2016
DOI: 10.1007/s40271-016-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Older Adults in Health Care Decision-Making: A Realist Synthesis

Abstract: BackgroundEngagement in healthcare decision making has been recognized as an important, and often lacking, aspect of care, especially in the care of older adults who are major users of the healthcare system.ObjectiveWe aimed to conduct a review of available knowledge on engagement in healthcare decision making with a focus on older patients and their caregivers.MethodsWe conducted a realist synthesis focusing on strategies for engagement of older patients and their caregivers in healthcare decision making. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 51 publications
(68 reference statements)
8
61
0
1
Order By: Relevance
“…Similarly to our study a review conducted by Elliot et al [27], described how for older adults engagement in healthcare decision-making is complex. How this occurs varies depending on the characteristics of the person and their situation.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly to our study a review conducted by Elliot et al [27], described how for older adults engagement in healthcare decision-making is complex. How this occurs varies depending on the characteristics of the person and their situation.…”
Section: Discussionsupporting
confidence: 57%
“…Studies have identified a number of factors that improve patient engagement in healthcare decisions including skills and knowledge, patient/provider relationships built on trust, good communication mechanisms and decreased confusion about choices 9 10. This study of Open Notes, similar to others,7 11 has shown that patients believe having access to notes improves their knowledge and communication with their providers and, notably, that easy access to their notes can improve trust with their providers.…”
mentioning
confidence: 76%
“…Primary care professionals confirmed that patients were often discharged from hospital with 'false hope' of cure because this information had not been conveyed, thus suggesting a dominant curative culture in secondary care. 39 Barriers to ensuring a smooth transition to palliative care in secondary care included the difficulty of 'standing back', professional hierarchies that limited the ability of junior medical and nursing staff to input into decisions on care and poor communication, 50 all of which can be suggested to contribute to the organisational culture of secondary care. Furthermore, it has been found that the diagnosis of dying in secondary care is often made late; this was accredited partly to prognostic uncertainty but also by a curative culture that did not acknowledge death as a possible outcome until it was imminent.…”
Section: Refined Programme Theorymentioning
confidence: 99%